FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS LUBUK UNEN KABUPATEN BENGKULU TENGAH - Rifda - Neni (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2022)
Ideally, babies should be breastfed within one hour of birth, exclusively breastfed for the first 6 months of life. In 2018, babies who received exclusive breastfeeding in Indonesia were 65.16%, while in 2019 babies who were exclusively breastfed experienced an increase of 67.74%. The purpose of this study was to study the factors associated with exclusive breastfeeding in the working area of ​​the Lubuk Unen Public Health Center, Central Bengkulu Regency. This study uses a quantitative approach to the type of analytical survey research, namely the Cross Sectional approach. The number of samples of 64 respondents was taken by purpusive sampling technique, data collection using primary data, processed and analyzed by univariate analysis and bivariate analysis with chi-square and contingency coefficient. The results obtained: from 64 mothers there were 39 mothers (60.9%) who gave exclusive breastfeeding to their babies, 38 mothers (59.4%) who had IMD, 45 mothers (70.3%) who received support from officers regarding the provision of breast milk. Exclusive breastfeeding, 35 mothers (54.7%) did not receive support from their husbands in exclusive breastfeeding. There is a relationship between the implementation of IMD, support from health workers with exclusive breastfeeding in the working area of ​​the Lubuk Unen Health Center, Central Bengkulu Regency, the category of weak relationship. It is hoped that the Lubuk Unen Health Center, Central Bengkulu Regency, is expected to increase the outreach of information sources about breastfeeding to infants in the community. Keywords: IMD, support from health workers, support from husbands, exclusive breastfeeding